Fifth Five-Year Plan of Orissa (Draft) - Planning Commission (Planning Commission, 1973)
Orissa’s backwardness in the midst of rich natural resources has often been described as a paradox; mere appropriately, it is an affirmation of the historical experience that resource availability is not a sufficient condition for economic change. In general, the crucial difference between a developed and a low-income economy lies not so much in the size of the resource base as in the degree of rational utilisation of its available resources, which in its turn depends on the quality of labour force and human resources, of technology and skills in production as also the level of employment of capital. The aim of planning in India as also in Orissa has been to bring about a high degree of rational utilisation of the existing resources, thereby initiating a process of development which will raise the living standards and open out new opportunities for a richer life for our people. The Fifth Five-Year Plan will also be a step in this direction. In the following paragraphs a review has been made of the socio-economic situation in Orissa prevailing on the eve of the Fifth Plan period so that this will provide the necessary background for systematic action during the years 1974-79.
Planning and Co-Ordination Department Government of Orissa